Gottfried Semper and the problem of historicism - Hvattum, Mari, 1966-; ebrary, Inc. (New York : Cambridge University Press, 2004)
Using key texts by the German architect and theorist Gottfried Semper, Mari Hvattum offers a reinterpretation of historicism, which is here viewed both as a philosophical outlook and as an architectural problem. Hvattum focuses on Semper's two major concerns: an understanding of the ontological significance of art and architecture, and the rendering of art and architecture as the objects of scientific investigation and prediction. Hvattum investigates the background and implications of these conflicting concerns. By examining the historicist fusion of Romanticism and Positivism, the book seeks to understand the nature as well as the limits of the modern dream of a 'method of inventing'. More than an intellectual biography, Gottfried Semper and the Problem of Historicism explores historicism and its implications for modern architectural discourse and practice.
Introduction : Gottfried Semper, texts and interpretations -- Part I: Towards a poetics of architecture -- 1, The cult of origins -- 2, The doctrine of imitation -- 3, Semper and the poetics of architecture -- Part II: Practical aesthetics -- 4, Semper and practical aesthetics -- 5, The comparative method -- 6, Towards a method of inventing -- Part III: The aporias of historicism -- 7, Semper and the "style of our time" -- 8, History and historicism -- 9, Between poetics and practical aesthetics
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: Semper, Gottfried, -- 1803-1879; 19. století; teorie umění -- Německo -- 19. století; teorie architektury -- Německo -- 19. století; filozofie umění; architektura -- filozofické aspekty; historismus; theory of art -- Germany -- 19th century; theory of architecture -- Germany -- 19th century; philosophy of art; architecture -- philosophical aspects; historicism; monografie; e-knihy online; monographs; e-books online